MANAGEMENT OF Amburana cearensis var. acreana IN ACRE STATE, BRAZIL - Evaldo Muñoz Braz (Ciência Florestal, 2014)
http://dx.doi.org/10.5902/1980509814586 This work has as its objectives: a) to assess the geographical distribution and population structure of Amburana cearensis var. acreana; b) to calculate sustainable cutting rates, according to stipulated cutting cycles, and c) to simulate the projected recovery potential in volume based on the calculated cutting rate. It was used data from sustainable forest management plans, and the results will contribute for future decisions about its endangered condition. The results did not corroborate the information that Amburana cearensis var. acreana is endangered in Acre state. However the management sustainability will only be feasible if considered the ideal remaining population structure and the estimative of the optimal cutting rate according to the cutting cycle.